Determination of vitamin C and minerals from spinach (Amaranthus viridis) chips for nutrients facts - Nurhazwani , Musa (2012)
The objective of this study is to determine the composition of vitamin C, iron (Fe), calcium (Ca) and potassium (K) that contain in spinach chips by using titration method and Atomic Absorption Spectrophotometer (AAS) method. Besides, the vitamin and minerals content that being determined were compared with other commercial chips such as banana chips and potato chips. This study was conducted due to the less food product that used vegetables as the main ingredient and provides the information whiéh is the nutrient fact for the spinach chips. The study involved the preparation of 100 g spinach (Amaranthus Viridis) chips and the analysis of Vitamin C using AOAC 967.21 test method and also the determination of mineral such as Fe, Ca and K using AOAC 968.08, composition of vitamin C was 0.1 % Fe was 965.09. The results showed that the 0.55 %, Ca was 16.29% and K was 14.18 % respectively. The total vitamin and minerals amount of nutrients were 4.8 mg/ 100 g for vitamin C, 814.9 mg/ kg for Ca, 27.4 mg/ kg for Fe and 709.8 mg/ kg for K. It was found that, spinach contained nutrients value even though it was cooked as chips. High nutrients value especially in vitamin C and minerals provide health benefits to human bodies.